Nietzsche, tipologia e hierarquia - Silva, Roni Lenon da (2016)
It has been having as supporter for some texts of the German philosopher Friedrich Nietzsche, the objective of this research is investigate the hierarchy (Rangordnung) and the concept of type (Typus). However, the intent this research doesn’t aim only to interpret the possible hierarchical relations between some types, but also extract this task some hierarchical criteria. The hierarchical criteria of the creation is developed, in a certain measure, as a conducting wire for the chapters, it has been interpreted in the following typological relations: free spirit, and captive spirit, tragic and Socratic, and lord and slave. About these types: Are all the creators? No, not all of them are creators, however, it is not only this characteristic that organizes the hierarchically types, but also the difference between their creations is an important distinguishing point: are signs of affirmation and courage in the face of life, or expressions of fatigue, self-indulgence, escape, fear, and hatred? Do the creations these types raise or impoverish man and life? The concept of creation as a criterion is interpreted – to a large measure – based on the discourse of Thus spoke Zarathustra, entitled, the three metamorphoses. Accordingly, the free spirit is creator, but only of itself exactly; it represents the lion for his courage, being a high hierarchical to be free of the current duties, as opposed to the camel. The camel is captive, because it does not create, only it usually reveres what it has already been created, it is accommodated to the present by its fear of creating. The Dionysian tragic is analogous to the spirit as a child, they both claim life and lie with the unceasing creation. The Socratic also creates, however, as a reaction to the mythological creation of the tragic, and as escape from existence, being more analogous to the camel for its unceasing belief and search of the truth. The Noble type is creator, and analogous to the child, therefore, when subordinating the plebeian type in favor of the creation and of cultivate of a superior type, it makes with innocence and without compassion. Another characteristic is that its creation comes itself from the affirmation and reverence, it is of the first command. The slave creates with hatred and resentment, reacting to the lord’s creation, being more analogous to the camel. Its creation enables an impoverishment, because it aims to conserve the majority, rather than strong type, it has been making this the last one corrupts itself, and it considers itself “bad” in contrast with the flock of “good” men.